Correlates of felt age in caregivers of people with dementia: findings from the IDEAL study - Sabatini, Serena; Turner, Shelbie G.; Morris, Robin G.; Opdebeeck, Carol; Thom, Jeanette M.; Hunt, Anna; Allan, Louise; Pentecost, Claire; Clare, Linda (Frontiers in Psychology, 2024)
Objective Family relationships influence how people appraise their own aging and how their appraisals impact their health. We analyzed felt age (FA) among family caregivers of people with dementia. Methods and measures We used a stratified sample of 1,020 spousal and 202 adult-child caregivers from the IDEAL study. We estimated cross-sectional associations and bidirectional influences between caregivers' FA and their health and wellbeing (depression, number of health conditions, stress, positive aspects of caregiving) over 2 years. Results Among spousal caregivers, 25% had a younger FA and 36% had an older FA. Among adult-child caregivers, 21.8% had a younger FA and 36.1% had an older FA. In spousal and adult-child caregivers an older FA was cross-sectionally associated with higher depression, number of health conditions, and stress, and fewer positive aspects of caregiving. In spousal caregivers, hours of care per day moderated the association between FA and depression, and FA was associated with stress 1 year later. Conclusion Caregiving may impact FA and its relationship with health. We urge continued research on the connections between caregiving and FA, and how interventions might support caregivers' positive views on their own aging, which will translate views on aging scholarship to meaningfully improve caregivers' lives.